2018
DOI: 10.1139/as-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Correlating tropical climate with survival of an Arctic-breeding, trans-equatorial migrant seabird

Abstract: Extreme climate can negatively affect survival through increased physiological demands or by reducing prey availability. This can have significant population-level consequences for organisms with low reproductive rates, such as seabirds. As an Arctic-breeding trans-equatorial migrant, Sabine’s gull (Xema sabini) is exposed to a profound variety of climate regimes during the year. Therefore, its annual survival may be affected by broad-scale teleconnection patterns that influence regional climate variability. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Consequently, our results suggesting apparent adult survival of 0.883 places Arctic terns in the Canadian High Arctic at similar survival to terns breeding further south in North America, including other Sterna species (Payo-Payo et al 2018) and a little lower than recent rates of other tern species (Ledwoń et al 2013). Moreover, adult tern survival was in the range of estimates for other Arctic larids breeding in Nunavut: glaucous gulls-0.84-0.86 (Gaston, Descamps et al 2009;Allard et al 2010); Thayer's gulls (Larus thayeri)-0.81 (Allard et al 2010) and Sabine's gulls (Xema sabini)-0.90 (Fife et al 2018).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Consequently, our results suggesting apparent adult survival of 0.883 places Arctic terns in the Canadian High Arctic at similar survival to terns breeding further south in North America, including other Sterna species (Payo-Payo et al 2018) and a little lower than recent rates of other tern species (Ledwoń et al 2013). Moreover, adult tern survival was in the range of estimates for other Arctic larids breeding in Nunavut: glaucous gulls-0.84-0.86 (Gaston, Descamps et al 2009;Allard et al 2010); Thayer's gulls (Larus thayeri)-0.81 (Allard et al 2010) and Sabine's gulls (Xema sabini)-0.90 (Fife et al 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Sandvik et al (2005) and Frederiksen et al (2008) showed that change underway in climatic conditions, or extreme weather events, have a deleterious effect on adult survival in other seabirds breeding in the North Atlantic. Long-distance migrants are expected to be even more vulnerable to climate variation (Both et al 2009), and evidence from sympatrically-nesting Sabine's gulls, another trans-equatorial migrant breeding at this site, found that annual survival was lower during anomalous climatic conditions in the wintering grounds or migration sites (Fife et al 2018). Interestingly, Sabine's gulls also deferred nesting in the two years that Arctic terns did; whether this was a response by both species to local climatic conditions (and resulting effects on foraging or nesting) or a response to conditions on the wintering or migration grounds is unknown.…”
Section: Discussionmentioning
confidence: 87%
“…As migratory species spend the majority of their annual cycle on migration or overwintering, the habitat conditions experienced during these periods are likely to influence adult and post-fledging juvenile survival. Likewise, conditions on breeding grounds influence reproductive success, with decreases in productivity in years where conditions are poorer (Fife et al, 2018). In addition to these within-season effects, conditions experienced in one season can affect the condition and performance of 4 individuals in later seasons (Harrison et al, 2011).…”
Section: Introductionmentioning
confidence: 99%